Structural Design, Synthesis, and Preliminary Biological Evaluation of Novel Dihomooxacalix[4]arene-Based Anti-tumor Agents - An, Lin; Wang, Chan; Han, Lili; Liu, Jiadong; Huang, Tonghui; Zheng, Youguang; Yan, Chaoguo; Sun, Jing (Frontiers in Chemistry, 2019)
Calixarene and its derivatives have been extensively served as promising anti-tumor agents. Previously, we have synthesized a series of calix[n]arene polyhydroxyamine derivatives (n=4, 6, 8) and found that 5,11,17,23-tetra-tert-butyl-25,27-bis [N-(2-hydroxyethyl) aminocarbonylmethoxyl] calix[4]arene (CLX-4) displayed significant effect toward SKOV3, A549, SW1990, HeLa, Raji, and MDA-MB-231 cancer cells. In the present work, we find a replacement of calix[4]arene bone and synthesized nineteen novel structurally related dihomooxacalix[4]arene amide derivatives 4A–4S to optimize its efficacy. Their abilities to induce cytotoxicity in Human lung carcinoma (A549) cells, breast cancer (MCF-7) cells, cervical cancer (HeLa) cells, hepatocellular carcinoma (HepG2) cells, as well as Human umbilical vein endothelial (HUVEC) cells are evaluated in vitro. The encouraging results show that the majority of dihomooxacalix[4]arene amide derivatives are effective at inhibiting A549 cell proliferation with the corresponding IC50 is ranging from 0.6 – 20.1 μM. In particular, compound 4A, 4D and 4L explore markedly increased potency (IC50 value is 2.0 ± 0.5 μM, 0.7 ± 0.1 μM and 1.7 ± 0.4 μM) over the cytotoxicity profiles of control CLX-4, whose IC50 value is 2.8 ± 0.3 μM. More interestingly, 4A also demonstrates the perfect cytotoxic effect against MCF-7, HeLa and HepG2 cells with IC50 value is 1.0 ± 0.1 μM, 0.8 ± 0.2 μM, and 2.7 ± 0.4 μM. In addition, the results proved that our synthesized 4A has much lower toxicity (41%) to normal cells at a concentration of 10 μM than that of 4D (90%). To reveal the mechanisms, the key indicators including the cell cycle and apoptos are observed by the flow cytometry analysis in MCF-7 cells. The results demonstrate that both 4A and 4D can induce the MCF-7 cell cycle arrest in G0/G1 phase and cell apoptosis. Therefore, our finding proves the dihomooxacalix[4]arene amide derivatives are convenient platforms for potential supramolecular anticancer agents.